Evaluative study: Strengthening teacher competence through utilization of the Merdeka Mengajar platform - Larasati; Hayat, Ainul; Novita, Asti Amelia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
The evaluation of the Merdeka Mengajar Platform Program at SMP Brawijaya Smart School aimed to determine the improvement of teacher competence, using the CIPP (Context, Input, Process, Product) evaluation model. The survey indicates that the Merdeka Mengajar Platform increases teachers’ digital workload, necessitating an evaluation of the program's effectiveness in supporting the four teacher competencies. This program evaluation employs a qualitative approach, utilizing Miles et al.'s (2014) interactive model through interviews, observations, and documentation involving the principal, vice principal, and teachers. The results showed that: (1) in terms of context, the platform is in line with government policies and supports improving teacher competencies; (2) in terms of inputs, human and physical resources are adequate; (3) in the process dimension, performance monitoring is conducted systematically; and (4) in terms of products, the platform has contributed to improving the four teacher competencies effectively. However, there are challenges related to time. This application remains feasible with adjustments, including simplifying the appearance and adding scheduling features, reminders, and estimated learning duration to accommodate teachers' limited time.